Cloud Condensation Nuclei in FIRE III - Hudson, James G.; Delnore, Victor E. (2002)
Yum and Hudson showed that the springtime Arctic aerosol is probably a result of long-range transport at high altitudes. Scavenging of particles by clouds reduces the low level concentrations by a factor of 3. This produces a vertical gradient in particle concentrations when low-level clouds are present. Concentrations are uniform with height when clouds are not present. Low-level CCN (cloud condensation nuclei) spectra are similar to those in other maritime areas as found by previous projects including FIRE 1 and ASTEX, which were also supported on earlier NASA-FIRE grants. Wylie and Hudson carried this work much further by comparing the CCN spectra observed during ACE with back trajectories of air masses and satellite photographs. This showed that cloud scavenging reduces CCN concentrations at all altitudes over the springtime Arctic, with liquid clouds being more efficient scavengers than frozen clouds. The small size of the Arctic Ocean seems to make it more susceptible to continental and thus anthropogenic aerosol influences than any of the other larger oceans.